M204. ULTRA-RESISTANT SCHIZOPHRENIA IS ASSOCIATED WITH A DELAY TO INITIATE CLOZAPINE AND WITH LESS ABDOMINAL OBESITY. SEX DIFFERENCES IN INSULINEMIA AND LEPTIN LEVELS ARE OBSERVED BETWEEN RESPONDERS AND NOT RESPONDERS. (18th May 2020) - Hönig, Guillermo; Rodante, Demián; Daray, Federico; Izaguirre, Mercedes; Lenze, Mariela; Valentini, Joaquín; García Bournissen, Facundo; Laura Gutiérrez, María; Wikinski, Silvia
Abstract: Background: 30% patients suffering from schizophrenia fail to obtain therapeutic benefit even after two appropriate antipsychotic trials and are considered resistant. The recommended treatment in these cases is clozapine (CLZ), but only 40% of patients with resistant schizophrenia show clinical response, a condition called ultra-resistance (UR) and defined as the lack of antipsychotic response after 8 to 12 weeks of treatment with at least 400 mg/day of clozapine or plasma levels ≥ 350 ng/ml. The objective of the present study is to identify factors associated with UR in in a group of patients from Argentina. Methods: A paired case-control study was conducted, being cases those patients with UR schizophrenia and controls those who responded to CLZ; both groups were matched by age and sex. The response to CLZ was measured using the PANSS (UR was defined with a total score ≥ 80). The following parameters were compared between groups: months of untreated psychosis, months until the introduction of clozapine, body mass index (BMI), waist circumference, fasting blood glucose, insulinemia, triglyceridemia, HDL cholesterol, ultrasensitive C-reactive protein (CRP) and plasma leptin levels. Clozapine and nor-clozapine plasma trough levels were measured by HPLC-MS/MS. Results: 9 men (M) and 7 women (W) with the diagnosis of UR schizophrenia were matched with the same number of responders (R) to clozapine. Total PANSS scores (mean ± SD) for each group were as follows: W-R 48.9 ± 11; W-UR 88.4 ± 6 (p < 0.0001); M-R 60.5 ± 7; M-UR 112.8 ± 23 (p < 0.0001). CLZ dose was significantly higher both in W-UR and in M-UR than in paired controls (p < 0.05). Nonsignificant differences were observed for nor-CLZ plasma concentration among groups. Clozapinemia was not different among men but it was significantly higher in W-UR in comparison with W-R (p < 0.05). Significant differences were detected in the amount of months that passed before initiation of CLZ both for women (W-R 140.9 ± 124, W-UR 255.6 ± 153, p < 0.005) and men (M-R 104.0 ± 51. 6 versus M-UR 174.6± 65; p < 0.05). Body mass index (kg/m2) was significantly lower in UR patients: W-R 35.3 ± 6 versus W-UR 26.9 ± 3 (p < 0.05) and M-R 30.6 ± 5 versus M-UR 22.7 ± 4 (p <.005). Waist circumference (cm) was also significantly lower in UR independently of sex: W-R 110.6 ± 12 versus W-UR 98.5 ± 8 (p < 0.05); M-R 113.9 ± 15 versus M-UR 87.4 ± 9 (p <0 .005). Insulinemia (UI/ml) was significantly lower in M-UR than in M-R (16.1± 8 versus 9.4 ± 7, p<0.005) but not in women. Also significant differences were found in leptin levels (pg/ml) in men but not in women (M-R 1824.0 ± 1139 versus M-UR 477.6 ± 692; p < 0.05). No differences were observed in the number of antipsychotics received before CLZ, months of untreated psychosis, fasting glycemia, trygliceridemia, HDL cholesterol, CRP, HbA1c and diastolic or systolic arterial blood pressure. Discussion: Time to CLZ initiation could be a critical factor predisposing to UR. The absence of clozapine-induced abdominal obesity and changes in BMI are also to be associated with poor clinical response, independently of plasma drug levels. Differences between ultra-resistant men and women concerning insulin and leptin plasma levels should be further investigated. As far as we know, this is the first paired case-control study aimed to investigate factors associated with CLZ resistance in schizophrenia.